Overcoming group conflicts in the process of professional adaptation of students - Гура [Gura E.] Едуард Іванович (Slobozhanskyi Herald of Science and Sport, 2013)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–> The investigation of ways to overcome educational group conflicts among 418 students during teaching practice in physical culture in Dnipropetrovsk higher educational establishments were carried out. It’s found out that 0,5 % students are in the group which has no chances to overcome group conflicts; 48,8 % are in the group,where the problems have tendency to prolongation; 37,1 % students are in groups in which the conflicts are developing and becoming more complicated; 13,6 % investigated study in groups in which the problems are successfully solved on rational basis. The results of the investigation are used for creation the adaptation training «Overcoming of group conflicts». <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>